POTENTIAL PROBLEMS OF INTERCULTURAL COMMUNICATION IN THE ACCULTURATION PROCESS AT PT MUTIARA AGAM: NIAS AND MINANG ETHNIC - Fikrani Suhma Azzuhra; Thaufiq Hidayat; Suhaimis Suhaimis (ORASI: Jurnal Dakwah dan Komunikasi, 2024)
Intercultural communication implies two cultures that meet often experience prejudice due to different languages. This way, the two ethnic groups acculturate to achieve the same communication patterns. This research aims to describe the potential intercultural communication problems at PT Mutiara Agam. This study uses a qualitative method with Larry A. Samovar's potential problem theory as the approach. Data collection techniques include interviews, observations, and documentation. Data analysis starts with data reduction, data display (data presentation), and conclusion drawing/verification. The research results show that intercultural communication at PT Mutiara Agam faced challenges due to the gap between Nias and Minang ethnic workers. Negative stereotypes, limited communication skills, attitudes of avoiding uncertainty, prejudice, and the tendency to withdraw from social interaction, as well as domination and ethnocentrism also complicated relationships. However, acculturation efforts were still carried out through flexible use of language, pig hunting activities as a means of cultural adaptation, and culinary adjustments, even though the Nias ethnic group tended to maintain the habit of eating pork. By providing an in-depth understanding of the dynamics of intercultural communication and adaptation and integration strategies, this article expands insight into the challenges and opportunities in achieving harmony in a culturally diverse work environment. This contribution is valuable for companies, practitioners, and researchers engaged in intercultural communication and human resource management.